Study of the formation of tungsten powder by hydrogen reduction of ammonium paratungstate and stereometric analyses of the powder texture. (15th January 2020) - Sadeghi, Mohammad; Rezaee, Sahar; Arman, Ali; Ţălu, Ştefan; Luna, Carlos; Shakoury, Reza
Abstract: The micromorphology of tungsten particles obtained by means of the annealing and hydrogen reduction of ammonium paratungstate (APT) has been finely analyzed during different formation stages using scanning electron microscopy (SEM). The intermediate tungsten oxides appearing during the different reactions were identified, and their particle morphologies were analyzed. The surface texture and texture isotropy of the final tungsten powder were investigated utilizing different methodologies. The surface segmentation using the watershed segmentation algorithm revealed fractal features.